Production and characterization of biodiesel from the traditional tannery fleshing wastes - Reda, A (Ethiopian Journal of Science and Technology, 2025)
The possibility of biodiesel production from traditional tannery fleshing wastes was investigated with respect to fuel properties. Based on worldwide standard procedures (ASTM specification), the biodiesel fuel properties such as iodine value, moisture content, free fatty acid, saponification value, acid value, viscosity, density, cetane number, higher heating value, and percentage yield were evaluated. The fleshing oil, which was investigated experimentally, had high acid value of 26.37 mg KOH/g and FFA level of 13.18%. As a result, acid pretreatment followed by base-catalyzed transesterification reaction was carried out to produce biodiesel. At the pretreatment stage, the acid value and FFA level were reduced to 3.93 mg KOH/g and 1.96%, respectively through sulfuric acid catalyzed esterification reaction.